If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying n + 4 + -3 = 10 Reorder the terms: 4 + -3 + n = 10 Combine like terms: 4 + -3 = 1 1 + n = 10 Solving 1 + n = 10 Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '-1' to each side of the equation. 1 + -1 + n = 10 + -1 Combine like terms: 1 + -1 = 0 0 + n = 10 + -1 n = 10 + -1 Combine like terms: 10 + -1 = 9 n = 9 Simplifying n = 9
| 6x+7=-6x-53 | | (2x^3)-x=0 | | .5x-3=.33x+5 | | 12sin^2x-2sinx-4=0 | | 103=15+4v | | 20+7i=(-3i) | | x(2x+5)=340 | | 3x=2x+6-6 | | 7.2/3 | | -(n+8)=8-3n | | 6x=21+7y | | 0.5*x+x=4.5 | | 4(y+2)=34 | | (4/9)^1/2 | | 0.5*x=4.5 | | 15c-6=8c+78 | | y=-7/2x | | 7(2x-5)=6x-11 | | -14f+14f=-10 | | -10a=-71 | | -16-6=v | | 3/5_____=300 | | 6a^4b^-3c^2/-10ab^6c^7 | | -8z(2z+3z^2+3z^3)= | | -12-3p=-6p-3p | | 3x-12=5x-26 | | 20c=30 | | 60.00=0.14x+29.95 | | (5)√(32/1024) | | n-(-2)+7=22 | | 5y+x-6=0 | | 5(2a-6)-3(4a-7)= |